Composite ceramic pump overflowing part, preparation method of composite ceramic pump overflowing part and composite ceramic pump
By using boron carbide particles and other materials to prepare the composite ceramic pump overflow parts, the problems of wear and corrosion of composite ceramic pumps in the prior art in the strong acid and alkali environment are solved, and higher wear resistance and acid and alkali resistance are achieved. Extend the service life of the equipment and reduce operating costs.
Patent Information
- Application Number
- CN202411252534.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
When the existing composite ceramic pump overflow parts are transported with fluids containing high concentrations of solid particles and corrosive chemicals, they are prone to wear and corrosion, resulting in short service life and high operating costs. Traditional wear-resistant alloy materials are in strong acid and alkali environments. Inadequate wear resistance.
Boron carbide particles are used as the main material, combined with silicon powder, binder, dispersant and curing agent, and composite ceramic materials are prepared by reacting and sintering after casting and molding to form a wear-resistant, acid- and alkali-resistant composite ceramic pump overflow part.
It significantly improves the wear resistance and acid and alkali resistance of the composite ceramic pump overflow parts, extends the service life of the equipment, reduces operating costs, and adapts to more complex working conditions.
Smart Images

Figure CN119118675A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flow-through parts, and in particular to a composite ceramic pump flow-through part and a preparation method thereof, as well as a composite ceramic pump. Background Art
[0002] Composite ceramic pumps are widely used in industries such as electricity, metallurgy, chemicals, mining, and hydraulics, primarily for conveying solid-liquid two-phase fluids containing high concentrations of solid particles. Currently, the design theory for composite ceramic pumps is still based on a modified version of the design theory for clean water centrifugal pumps. These slurries contain not only a large number of solid particles but also various corrosive chemicals, which can easily cause wear and corrosion of the composite ceramic pump's flow-through components, reducing the pump's lifespan.
[0003] At present, the flow passage parts of composite ceramic pumps in China are mainly made of wear-resistant alloy materials, which have a short service life. In particular, when transporting slurries with heavy abrasion, strong acids and alkalis, the service life of traditional composite ceramic pumps is very short, and the working time is only half a month or even a week. Once the flow passage parts are damaged, the pump needs to be stopped and replaced. The flow passage parts of the pump are expensive, have a short service life, and spare parts need to be replaced frequently, which has high operating costs and affects the normal production and operation of the company. Alumina or silicon carbide combined with silicon nitride materials are also currently used. Although this material has better wear resistance than traditional wear-resistant alloys, it has poor resistance to strong alkalis and cannot adapt to complex working conditions. Therefore, it is necessary to develop a composite ceramic pump flow passage material that is both wear-resistant and acid- and alkali-resistant and suitable for a variety of complex environments to increase the service life of the composite ceramic pump. Summary of the Invention
[0004] One of the purposes of the present invention is to provide a composite ceramic pump flow part in response to the above-mentioned shortcomings and defects of the prior art. The composite ceramic pump flow part utilizes the high hardness and acid and alkali resistance of boron carbide to form a wear-resistant and corrosion-resistant composite ceramic pump flow part material.
[0005] A composite ceramic pump flow part, the raw materials for preparing the preform thereof, comprising the following components in percentage by weight:
[0006] Boron carbide particles 70w%-85w%,
[0007] Binder 8w%-15w%,
[0008] Dispersant 0.1w%-0.5w%,
[0009] Curing agent 0.2w%-0.5w%,
[0010] Silicon powder 10w%-20w%.
[0011] In a preferred embodiment of the present invention, the size of the boron carbide particles is 7-200 mesh, and the size of the silicon powder is 200-325 mesh.
[0012] In a preferred embodiment of the present invention, the binder includes at least one of silica sol, aluminum sol, gum arabic, sodium carboxymethyl cellulose, and lignin dextrin.
[0013] In a preferred embodiment of the present invention, the dispersant includes at least one of PPG200, sodium tripolyphosphate, and sodium hexametaphosphate.
[0014] In a preferred embodiment of the present invention, the curing agent includes at least one of citric acid monohydrate, sodium fluorosilicate, and calcium hydroxide.
[0015] The second purpose of the present invention is to provide a method for preparing a composite ceramic pump flow part, in which a boron carbide-based composite ceramic material is prepared by reaction sintering after casting. It has better wear resistance than traditional wear-resistant metals and ordinary ceramic materials, and has stronger acid and alkali resistance.
[0016] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0017] Step 1: Obtain raw materials for preparing a preform according to a composite ceramic pump flow component as described in any of the above technical solutions;
[0018] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0019] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0020] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0021] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0022] Step 6: First evacuate the chamber, then introduce nitrogen. In a nitrogen atmosphere, keep the temperature at 600°C for 4-12 hours. After nitriding is completed at 1450°C, continue to heat the chamber to 1550-1700°C and keep the temperature for 4-6 hours.
[0023] In a preferred embodiment of the present invention, step 6: placing the embryo body in a sintering furnace, under a nitrogen atmosphere, heating from room temperature to 600°C and keeping it warm for 4-12 hours, reducing the heating rate and heating to 1450°C, keeping it warm for 24-48 hours, and after the insulation is completed, heating to 1550-1700°C and keeping it warm for 4-6 hours, and finally cooling it to room temperature with the furnace under the protection of a nitrogen atmosphere.
[0024] In a preferred embodiment of the present invention, the temperature is increased at 2°C / min before reaching 1200°C.
[0025] The third purpose of the present invention is to provide a composite ceramic pump. The composite ceramic pump utilizes the above-mentioned composite ceramic pump flow parts, which can effectively extend the working life of the composite ceramic pump in application, reduce the cost of use, and is beneficial to the enterprise's cost reduction and efficiency improvement.
[0026] A composite ceramic pump comprises a composite ceramic pump flow component as described in any of the above technical solutions.
[0027] Due to the adoption of the above technical solution, the composite ceramic pump flow parts of the present invention utilize the high hardness and acid and alkali resistance of boron carbide to form wear-resistant and corrosion-resistant composite ceramic pump flow parts materials. The preparation method of the composite ceramic pump flow parts of the present invention uses boron carbide as the main material with extremely high hardness. The boron carbide-based composite ceramic material is prepared by reaction sintering after casting. It has better wear resistance than traditional wear-resistant metals and ordinary ceramic materials, and has stronger acid and alkali resistance; it can adapt to more complex working environments, and the wear resistance test and acid and alkali resistance test results are better than wear-resistant alloys and aluminum oxide / silicon carbide combined with silicon nitride materials. The composite ceramic pump of the present invention utilizes the above-mentioned composite ceramic pump flow parts, which can effectively extend the working life of the composite ceramic pump in application. It can be used stably for a long time under the conditions of super-heavy slurry in steel mills and high corrosion in chemical plants, reducing the cost of use and benefiting the enterprise to reduce costs and increase efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 The present invention is a process flow chart of a method for preparing a composite ceramic pump flow component.
[0030] Figure 2 It is a sintering flow chart of the present invention. DETAILED DESCRIPTION
[0031] The preferred embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although preferred embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. Rather, these embodiments are provided to make the present invention more thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0032] The terms used in this invention are for the purpose of describing specific embodiments only and are not intended to limit the invention. The singular forms "a," "the," and "the" used in this invention and the appended claims are also intended to include plural forms unless the context clearly indicates otherwise. It should also be understood that the term "and / or" as used herein refers to and includes any or all possible combinations of one or more of the associated listed items.
[0033] It should be understood that although the terms "first", "second", "third", etc. may be used to describe various information in the present invention, such information should not be limited to these terms. These terms are only used to distinguish information of the same type from each other. For example, without departing from the scope of the present invention, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of such features. In the description of the present invention, "plurality" means two or more, unless otherwise clearly and specifically defined.
[0034] A composite ceramic pump flow part, the raw materials for preparing the preform thereof, comprising the following components in percentage by weight:
[0035] Boron carbide particles 70w%-85w%,
[0036] Binder 8w%-15w%,
[0037] Dispersant 0.1w%-0.5w%,
[0038] Curing agent 0.2w%-0.5w%,
[0039] Silicon powder 10w%-20w%.
[0040] The size of the boron carbide particles is 7-200 mesh, and the size of the silicon powder is 200-325 mesh.
[0041] The binder includes at least one of silica sol, aluminum sol, gum arabic, sodium carboxymethyl cellulose and lignin dextrin.
[0042] The dispersant includes at least one of PPG200, sodium tripolyphosphate, and sodium hexametaphosphate.
[0043] The curing agent includes at least one of citric acid monohydrate, sodium fluorosilicate, and calcium hydroxide.
[0044] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0045] Step 1: Obtain raw materials for preparing a preform according to the above-mentioned composite ceramic pump flow component;
[0046] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0047] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0048] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0049] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0050] Step 6: First evacuate the chamber, then introduce nitrogen. In a nitrogen atmosphere, keep the temperature at 600°C for 4-12 hours. After nitriding is completed at 1450°C, continue to heat the chamber to 1550-1700°C and keep the temperature for 4-6 hours.
[0051] Example 1
[0052] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0053] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 70 wt% of boron carbide particles; 10 wt% of a binder; 0.2 wt% of a dispersant; 0.5 wt% of a curing agent; 20 wt% of silicon powder; 7-200 mesh boron carbide particles; and 200-325 mesh silicon powder.
[0054] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0055] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0056] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0057] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0058] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it for 4-12 hours. Reduce the heating rate and heat it to 1450℃ and keep it for 24-48 hours. After the heat preservation is completed, heat it to 1550-1700℃ and keep it for 4-6 hours. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0059] Example 2
[0060] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0061] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 75wt% boron carbide particles; 10wt% binder; 0.2wt% dispersant; 0.5wt% curing agent; 15wt% silicon powder; boron carbide particles 7-200 mesh; silicon powder 200-325 mesh;
[0062] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0063] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0064] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0065] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0066] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it for 4-12 hours. Reduce the heating rate and heat it to 1450℃ and keep it for 24-48 hours. After the heat preservation is completed, heat it to 1550-1700℃ and keep it for 4-6 hours. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0067] Example 3
[0068] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0069] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 80 wt% of boron carbide particles; 10 wt% of a binder; 0.2 wt% of a dispersant; 0.5 wt% of a curing agent; 10 wt% of silicon powder; 7-200 mesh boron carbide particles; and 200-325 mesh silicon powder.
[0070] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0071] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0072] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0073] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0074] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it for 4-12 hours. Reduce the heating rate and heat it to 1450℃ and keep it for 24-48 hours. After the heat preservation is completed, heat it to 1550-1700℃ and keep it for 4-6 hours. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0075] Example 4
[0076] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0077] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 75wt% boron carbide particles; 8wt% binder; 0.2wt% dispersant; 0.5wt% curing agent; 17wt% silicon powder; boron carbide particles 7-200 mesh; silicon powder 200-325 mesh;
[0078] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0079] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0080] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0081] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0082] Step 6: Place the embryo in a sintering furnace and, under a nitrogen atmosphere, heat the embryo from room temperature to 600°C and hold for 4-12 hours. Then, reduce the heating rate and heat it to 1450°C and hold for 24-48 hours. After the holding period, heat it to 1550-1700°C and hold for 4-6 hours. Finally, cool it to room temperature in a nitrogen atmosphere.
[0083] Example 5
[0084] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0085] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 75wt% boron carbide particles; 15wt% binder; 0.2wt% dispersant; 0.5wt% curing agent; 10wt% silicon powder; boron carbide particles 7-200 mesh; silicon powder 200-325 mesh;
[0086] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0087] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0088] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0089] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0090] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it for 4-12 hours. Reduce the heating rate and heat it to 1450℃ and keep it for 24-48 hours. After the heat preservation is completed, heat it to 1550-1700℃ and keep it for 4-6 hours. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0091] Comparative Example 1
[0092] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0093] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 75wt% silicon carbide particles; 10wt% binder; 0.2wt% dispersant; 0.5wt% curing agent; 15wt% silicon powder; 7-200 mesh silicon carbide particles; 200-325 mesh silicon powder;
[0094] Step 2: Mix silicon carbide particles with silicon powder according to the particle size distribution;
[0095] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0096] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0097] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0098] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it for 4-12 hours. Reduce the heating rate and heat it to 1450℃ and keep it for 24-48 hours. After the heat preservation is completed, heat it to 1550-1700℃ and keep it for 4-6 hours. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0099] Comparative Example 2
[0100] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0101] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 75 wt% alumina particles; 10 wt% binder; 0.2 wt% dispersant; 0.5 wt% curing agent; 15 wt% silicon powder; 7-200 mesh alumina particles; 200-325 mesh silicon powder;
[0102] Step 2: Mix the alumina particles with silicon powder according to the particle size distribution;
[0103] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0104] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0105] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0106] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it for 4-12 hours. Reduce the heating rate and heat it to 1450℃ and keep it for 24-48 hours. After the heat preservation is completed, heat it to 1550-1700℃ and keep it for 4-6 hours. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0107] Comparative Example 3
[0108] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0109] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 65wt% of boron carbide particles; 10wt% of binder; 0.2wt% of dispersant; 0.5wt% of curing agent; 25wt% of silicon powder; 7-200 mesh of boron carbide particles; and 200-325 mesh of silicon powder.
[0110] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0111] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0112] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0113] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0114] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it for 4-12 hours. Reduce the heating rate and heat it to 1450℃ and keep it for 24-48 hours. After the heat preservation is completed, heat it to 1550-1700℃ and keep it for 4-6 hours. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0115] Comparative Example 4
[0116] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0117] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 85 wt% of boron carbide particles; 10 wt% of binder; 0.2 wt% of dispersant; 0.5 wt% of curing agent; 5 wt% of silicon powder; 7-200 mesh of boron carbide particles; and 200-325 mesh of silicon powder.
[0118] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0119] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0120] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0121] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0122] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it for 4-12 hours. Reduce the heating rate and heat it to 1450℃ and keep it for 24-48 hours. After the heat preservation is completed, heat it to 1550-1700℃ and keep it for 4-6 hours. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0123] Comparative Example 5
[0124] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0125] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 75wt% boron carbide particles; 18wt% binder; 0.2wt% dispersant; 0.5wt% curing agent; 7wt% silicon powder; boron carbide particles 7-200 mesh; silicon powder 200-325 mesh;
[0126] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0127] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0128] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0129] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0130] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it for 4-12 hours. Reduce the heating rate and heat it to 1450℃ and keep it for 24-48 hours. After the heat preservation is completed, heat it to 1550-1700℃ and keep it for 4-6 hours. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0131] Comparative Example 6
[0132] A method for preparing a composite ceramic pump flow component comprises the following steps:
[0133] Step 1: Obtain raw materials for preparing a preform, wherein the components by weight percentage are: 75wt% boron carbide particles; 10wt% binder; 0.2wt% dispersant; 0.5wt% curing agent; 15wt% silicon powder; boron carbide particles 7-200 mesh; silicon powder 200-325 mesh;
[0134] Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution;
[0135] Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry.
[0136] Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold;
[0137] Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece.
[0138] Step 6: Place the embryo in a sintering furnace, and in a nitrogen atmosphere, heat it from room temperature to 600℃ and keep it there for 4-12 hours. Then reduce the heating rate and heat it to 1450℃ and keep it there for 24-48 hours. After the end of the heating, do not continue to heat it. Finally, cool it to room temperature in the furnace under the protection of nitrogen atmosphere.
[0139] Comparative Example 7
[0140] The use of wear-resistant alloy steel materials to prepare flow-through parts is an existing technology and will not be described in detail here.
[0141] The material distribution between each embodiment and comparative example is shown in Table 1 below.
[0142] Table 1
[0143]
[0144] Density determination: The boiling method involves placing a constant-weight sample into an automatically controlled heating device filled with distilled water. Clean gauze is placed between the samples and on the bottom of the container to prevent contact between the samples. During the boiling process, the water level should be kept 50 mm above the sample. The distilled water is heated to a boil for 2 hours, then the water is removed and allowed to cool to room temperature. This method is also used to determine apparent porosity and the ratio of bulk density to theoretical density.
[0145] Wear rate calculation: Wear volume is measured using an MMH-5 three-body abrasive wear tester, using 7-150 mesh quartz sand, a test load of 40N, a rotational speed of 50 rpm, and 20 abrasion cycles per specimen, each lasting 5 hours. A larger wear volume value indicates poorer wear resistance. The ratio of the wear volume to the total volume of the specimen is the wear rate.
[0146] Acid and alkali resistance: Use distilled water to prepare 3 mol / L sulfuric acid and 6 mol / L sodium hydroxide, heat to a slightly boiling state and add them to a beaker. Put ten samples in each time and keep them for 24 hours. After the corrosion test is completed, take them out and rinse them thoroughly with distilled water or deionized water. Put them in an oven at 105℃-120℃ and dry them to constant weight. Weigh the weight and calculate the loss rate.
[0147] The comparison of the effects of the above performances between the embodiments and comparative examples is shown in Table 2.
[0148]
[0149] Based on the experimental results of the above examples and comparative examples, it can be seen that composite ceramic pump flow components prepared with boron carbide in the range of 70-80wt% and silicon powder in the range of 10-20wt% exhibit excellent wear resistance and corrosion resistance, especially significantly improved alkali resistance, surpassing the silicon carbide-based and alumina-based materials of Comparative Examples 1 and 2. Their overall performance far exceeds that of wear-resistant alloys. Referring to Comparative Example 6 and Example 2, the example in which the temperature was continued to rise after nitriding was completed had a higher density and improved wear resistance and acid and alkali resistance.
[0150] A composite ceramic pump, wherein the flow passage of the composite ceramic pump utilizes the aforementioned composite ceramic pump flow passage, while the rest of the composite ceramic pump utilizes existing technology. In application, the composite ceramic pump can effectively extend its service life, reduce its operating costs, and contribute to cost reduction and efficiency improvement for enterprises.
[0151] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.
Claims
1. A composite ceramic pump flow part, characterized in that: The raw materials for preparing the preform include the following components in percentage by weight: Boron carbide particles 70w%-85w%, Binder 8w%-15w%, Dispersant 0.1w%-0.5w%, Curing agent 0.2w%-0.5w%, Silicon powder 10w%-20w%.
2. A composite ceramic pump flow piece according to claim 1, characterized in that: The size of the boron carbide particles is 7-200 mesh, and the size of the silicon powder is 200-325 mesh.
3. The composite ceramic pump flow piece according to claim 1, characterized in that: The binder includes at least one of silica sol, aluminum sol, gum arabic, sodium carboxymethyl cellulose, and lignin dextrin.
4. The composite ceramic pump flow component according to claim 1, characterized in that: The dispersant includes at least one of PPG200, sodium tripolyphosphate, and sodium hexametaphosphate.
5. The composite ceramic pump flow component according to claim 1, characterized in that: The curing agent includes at least one of citric acid monohydrate, sodium fluorosilicate, and calcium hydroxide.
6. A method for preparing a composite ceramic pump flow component according to any one of claims 1 to 5, characterized in that: The steps include: Step 1: Obtain raw materials for preparing the preform; Step 2: Mix the boron carbide particles with silicon powder according to the particle size distribution; Step 3: Add the binder and dispersant and continue stirring. Finally, add the curing agent and stir to form a slurry. Step 4: Cast the slurry into a plaster mold, let it stand at room temperature, then place it in an insulated box for a period of time, and remove it from the mold; Step 5: Place the demoulded test piece in an oven at 150-200℃ for 5-12 hours to increase the strength of the test piece. Step 6: First evacuate the chamber, then introduce nitrogen. In a nitrogen atmosphere, keep the temperature at 600°C for 4-12 hours. After nitriding is completed at 1450°C, continue to heat the chamber to 1550-1700°C and keep the temperature for 4-6 hours.
7. The method for preparing a composite ceramic pump flow component according to claim 6, characterized in that: Step 6: First evacuate the chamber, then introduce nitrogen. In a nitrogen atmosphere, heat the chamber from room temperature to 600°C and keep it warm for 4-12 hours to remove some organic matter. Reduce the heating rate and heat the chamber to 1450°C and keep it warm for 24-48 hours. After the insulation is completed, heat the chamber to 1550-1700°C and keep it warm for 4-6 hours. Finally, cool the chamber to room temperature in the furnace under the protection of a nitrogen atmosphere.
8. The method for preparing a composite ceramic pump flow component according to claim 7, characterized in that: Before 1200°C, the temperature was increased at 2°C / min.
9. A composite ceramic pump, comprising a composite ceramic pump flow component according to any one of claims 1 to 9.
